2016
DOI: 10.3892/mmr.2016.5489
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of postnatal hippocampal neural stem cells generates nuclear receptor related-1 protein- and tyrosine hydroxylase-expressing cells

Abstract: Parkinson's disease (PD) is a severe neurodegenerative disorder. Although the detailed underlying molecular mechanism remains to be elucidated, the major pathological feature of PD is the loss of dopaminergic (DA) neurons of the substantia nigra. The use of donor stem cells to replace DA neurons may be a key breakthrough in the treatment of PD. In the present study, the growth kinetics of hippocampal neural stem cells (Hip-NSCs) isolated from postnatal mice and cultured in vitro were observed, specifically the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that Nurr1 directly regulates the promoter of TH gene (37). Upon activation, Nurr1 translocates to the nucleus, where it binds to the promoter region and activates the transcription of TH (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Nurr1 directly regulates the promoter of TH gene (37). Upon activation, Nurr1 translocates to the nucleus, where it binds to the promoter region and activates the transcription of TH (38).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on NSCs' direct differentiation toward specific subtypes of neurons is the hotspot. A bunch of studies reported the generation of dopaminergic neurons from NSCs (Ding et al 2016;Lee et al 2016a, b). Due to the fact that degradation of dopaminergic neurons plays key roles in the pathology of Parkinson's disease (PD), development of stem cell-based therapy is one of the most promising way in the treatment of PD (Zhu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To induce neuronal differentiation, the medium was replaced with serum-free Neurobasal medium (Gibco BRL, Gaithersburg, MD) supplemented with B27 (Gibco BRL, Gaithersburg, MD), Glutamax (Gibco-Invitrogen, Grand Island, NY), and 200 nM cytosine arabinoside (Sigma-Aldrich, St. Louis, MO). For copper accumulation assay, copper (1 μg/ml) was added into the culture medium along with copper chloride (1 μg/μL, Sigma-Aldrich, St. Louis, MO) as previously described ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%